2016
DOI: 10.1186/s12879-016-1788-4
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile infection health disparities by race among hospitalized adults in the United States, 2001 to 2010

Abstract: BackgroundRecognition of health disparities in Clostridium difficile infection (CDI) is an initial step toward improved resource utilization and patient health. The purpose of this study was to identify health disparities by black vs. white race among hospitalized adults with CDI in the United States (U.S.) over 10 years.MethodsThis was a retrospective analysis of the U.S. National Hospital Discharge Surveys from 2001 to 2010. Eligible cases included adults with an ICD-9-CM code for CDI (008.45). Patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 31 publications
1
39
1
1
Order By: Relevance
“…We suspect that this discrepancy was due to differences in the access of FMT between blacks and whites, which may be caused by disparities such as health insurance coverage, clinical access, and adequacy of long-term follow-up. Our findings are in keeping with recent studies showing health disparity and consequently use of medical services for CDI among different races 11 13 Alternatively, due perhaps to some cultural belief, black patients may find FMT less acceptable, especially when performed by colonoscopy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We suspect that this discrepancy was due to differences in the access of FMT between blacks and whites, which may be caused by disparities such as health insurance coverage, clinical access, and adequacy of long-term follow-up. Our findings are in keeping with recent studies showing health disparity and consequently use of medical services for CDI among different races 11 13 Alternatively, due perhaps to some cultural belief, black patients may find FMT less acceptable, especially when performed by colonoscopy.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in keeping with recent studies showing health disparity and consequently use of medical services for CDI among different races. 11,13 Alternatively, due perhaps to some cultural belief, black patients may find FMT less acceptable, especially when performed by colonoscopy. Therefore, they did not want to be referred for FMT.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown lower rates of CDI in both adult and pediatric populations among non-white subjects. 19,34 Our study had some limitations. This retrospective study was limited to available data in the electronic health record, which may lead to an incomplete assessment of symptoms and all potential risk factors of community-acquired CDI.…”
Section: Discussionmentioning
confidence: 94%
“…Age is a known risk factor for CDI, 21 and higher rates of CDI in whites and the Northeast have been demonstrated previously in the NHDS. 27,28 CDI rates were also related to admission status (elective vs not) with patients with cancer and CDI more likely to have emergent/urgent admissions. The rate of CDI in patients with cancer increased overall during the study period, with a peak incidence in 2007 to 2008.…”
Section: Discussionmentioning
confidence: 99%
“…-2002 2003-2004 2005-2006 Year 2007-2008 20092001-2002 2003-2004 2005-2006 Year 2007-2008 20092001-2002 2003-2004 2005-2006 Year 2007-2008 2009 …”
unclassified